PERLAKUAN ETHYL METHANE SULFONATE (EMS) PADA ENTEROBACTER AEROGENES AY-2 DARI LIMBAH METAN FERMENTASI UNTUK PENINGKATAN PRODUKSI GAS HIDROGEN - Rachman, Mahyudin Abdul (Jurnal Rekayasa Lingkungan)
Enterobacter aerogenes AY-2 mutant is known for hydrogen gas producer which ws obtained from the sludge of methane fermentation and the yield is 1.5 fold higher than wildtype. Hydrogen gas production can be gain via NADH oxidation in anaerobic metabolic pathway by blocking organic acid production. Metabolic pathway can be changed by mutagenesis. Enterobacter aerogenes AY-2 mutated with ethyl methane sulfonate in logarithmic phase with consentration 10, 11, 12, 13, 14 and 15 ?l/ml cell suspention during 120 minute. Mutation that result lowest survival ratio (0,01%) was 14 ?l EMS/ml cell suspention is repeated with variation incubation time, 30, 60, 90 and 120 minute. 166 double mutant colony has been collected and choosen randomly. The choosen 43 colony was fermented in glycerol complex medium for determining ten double mutant with the highest H2 production. Double mutant AD-H43 is a highest H2 producer that increase 20% H2 production from AY-2 and has a decrease lactid acid production, 31% less from AY-2. Increasing H2 production in double mutant AD-H43 is caused by lactate dehydrogenase deffi cient.Keywords: Enterobacter aerogenes AY-2, ethyl methane sulfonate (EMS), H2 and methane sludge